1988
DOI: 10.1038/eye.1988.140
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the formation of epiretinal membranes

Abstract: SummaryIn this review of the literature evidence is provided from clinical, histological and experimental sources that inflammatory processes play a central role in the pathogenesis of contractile epiretinal membranes and proliferative vitreoretinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 62 publications
1
19
0
1
Order By: Relevance
“…A recent study reported a 3.0% incidence of this occurrence at 11.6 months on average [24]. This incidence rate is comparable to our results that identified 4 such cases among 62 eyes (6.5%) over a period of 24 months.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study reported a 3.0% incidence of this occurrence at 11.6 months on average [24]. This incidence rate is comparable to our results that identified 4 such cases among 62 eyes (6.5%) over a period of 24 months.…”
Section: Discussionsupporting
confidence: 80%
“…Both enzymes have similar substrate specificities but whilst MMP-9 is released within hours, MMP-2 is expressed 3-4 days after injury. This may explain the relative absence of MMP-9 and the widespread distribution of MMP-2 within retinal membranes, which are solely associated with chronic inflammation (Gilbert et al, 1988). MMP-2 may be found in inactive form in normal vitreous (Brown et al, 1994) and aqueous humour (Girolamo et al, 1996), and a recent study shows the presence of MMP-2 and TIMP-2 in vitreous from eyes with PVR and other vitreo-retinal disorders (De La Paz et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Retinal membranes are composed of retinal pigment epithelial cells, glial cells, astrocytes and fibroblasts (Gilbert et al, 1988 ;Jerdan et al, 1989), in addition to infiltrating macrophages and lymphocytes (Limb et al, 1993 ;Weller, Heimann and Wiedemann, 1988). All these cells are bound into a framework of extracellular matrix proteins composed of collagen, fibronectin, vitronectin and laminin (Rodriguez, Newsome and Machemer, 1981 ;Weller et al, 1991 ;Scheiffarth et al, 1988), which confers contractibility to retinal membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inflammatory mediators promote fibrovascular growth in the setting of secondary ERM formation. 11 It could be possible that a prior intraocular inflammatory insult could result in eventual formation of focal choroidal scarring as well as ERM, resulting in the coexistence of both entities.…”
Section: Discussionmentioning
confidence: 99%